The Agglutination Action of Mannan Binding Protein (Lectin) Against Some Local Isolates of Pathogenic Bacterial - الجميلي, عصام; العبيدي, ريما; نادر, محمد (Iraqi Journal of Science, 2025)
The purified Serum mannan protein (Lectin) exhibited antibacterial properties against some isolates of some Gram -negative pathogenic bacteria by silde agglutination test .They were clear that the (SMBP) has the ability to agglutinate Salmonella choleraesuius, Shigella dysenteriae. We studied the effect of lectin toward E.coli and Klebsiella pneumoniae by using spectrophotometric assay which it was found to agglutination all dilutions of E.coli cells and gave high agglutination activity to wards the first three dilutions, and it improved weak agglutination activity towards Staphylococcus aureus which gave agglutine in 1/2 dilution only.